The Effect of Triethanolamine Variations on The Evaluation of Physical Properties of Papaya Leaf Ethanol Extract Lotion (Carica Papaya L.) - Susi Endrawati; Anom Parmadi; Sri Saptuti Wahyuningsih (Universitas Duta Bangsa Surakarta, 2026)
Background: Papaya leaves (Carica papaya L.) contain papain, flavonoids, and vitamin C, which have antioxidant potential. Objective: This study aimed to formulate papaya leaf ethanol extract as a lotion and to determine the effect of triethanolamine (TEA) concentration on its physical properties. Methods: This experimental study used 96% ethanol for maceration. Papaya leaf extract was incorporated at a concentration of 15%, while TEA concentrations were varied at 2% (F1), 3% (F2), and 4% (F3). The formulations were evaluated for organoleptic properties, pH, homogeneity, spreadability, adhesion, protective ability, lotion type, physical stability, preference, and viscosity. Results: The extract yield was 8.79% w/w. F1 and F2 were medium-viscosity liquids, whereas F3 was a low-viscosity liquid. All formulations were bright brownish-green, had a rose fragrance, were homogeneous, had a pH of 6, and formed oil-in-water (O/W) lotions. The highest mean spreadability under a 100 g load was 25.53 cm² in F2 and F3, whereas F1 showed the lowest value of 18.10 cm². The mean adhesion times were 1.56 s, 1.66 s, and 1.88 s for F1, F2, and F3, respectively. F3 was the most preferred formula, selected by 45% of respondents. All formulas remained stable during four weeks of storage. One-way ANOVA showed that TEA concentration significantly affected spreadability (p = 0.000) but did not significantly affect adhesion (p = 0.788). Conclusion: Papaya leaf ethanol extract can be formulated into a stable O/W lotion. Increasing the TEA concentration reduced viscosity and increased spreadability; however, the difference in adhesion was not statistically significant.